Sports training technologies: Achieving and assessing transfer - Gray, R. (Skill acquisition in sport: research, theory and practice, 2020)
In recent years there has been a proliferation of new technologies designed for training perceptual-cognitive skills in athletes. Some examples include Neurotracker, STRIVR, stroboscopic glasses, gameSense sports, Fit Light, Halo Sport and DeCervo to name a few. How can a coach, athlete or team manager determine whether any of these technologies are worth the financial investment? How should we be assessing the effectiveness of new sports training technologies? What factors should future technology designers be taking into account? In this chapter, it is argued that the gold standard for any sports training technology should be the achievement of high, positive transfer of training to performance during game play/competition. This chapter begins by exploring the different conceptualizations and dimensions of "transfer of training" as they apply to sport. Next, how transfer of training should be assessed from the perspective of experimental design and data analysis is considered. Finally, an attempt is made to summarise what has been learned from the relatively small number of studies on transfer of training using sports technologies. The chapter concludes with some suggestions for future research.